2022
DOI: 10.1093/ptep/ptac004
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of exotic hyperon halos in neutron-rich Zr hypernuclei

Abstract: We study the single- and double-Λ hypernuclei in Zr isotopes by Hartree-Fock-Bogoliubov model with Skyrme-type nucleon-nucleon, Λ-nucleon, and Λ-Λ interactions. We found two peculiar features of the Λ hyperon halo phenomena, which were never found in nuclei without the strangeness degree of freedom. One is the d-wave halo, and the other is the bunch of three halo orbits just below the Λ hyperon threshold in $^{137}_\Lambda$Zr and also $^{138}_{\Lambda \Lambda }$Zr. We name these exotic halo phenomena “ giant h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…The multidimensionally constrained RMF model has been used to study the shape evolution of hypernuclei in argon hyperisotopes [54]. The beyond meanfield approach has been utilized to discuss the evolution of p-state energies and composition in carbon hyperisotopes [24], as well as the hyperon halo structures in boron and carbon hyperisotopes [27,29]. These studies revealed the significance of the role of isospin in the description of hypernuclear structure.…”
Section: λ Snmentioning
confidence: 99%
See 1 more Smart Citation
“…The multidimensionally constrained RMF model has been used to study the shape evolution of hypernuclei in argon hyperisotopes [54]. The beyond meanfield approach has been utilized to discuss the evolution of p-state energies and composition in carbon hyperisotopes [24], as well as the hyperon halo structures in boron and carbon hyperisotopes [27,29]. These studies revealed the significance of the role of isospin in the description of hypernuclear structure.…”
Section: λ Snmentioning
confidence: 99%
“…The integration can be computed using the radial wave functions of the initial and final single-Λ states (see Ref. [27] for details).…”
Section: Dd-lz1-λ1mentioning
confidence: 99%